Endoscopic Alcohol Injection Therapy of Giant Gastric Leiomyomas: An Alternative Method to Surgery - Burhan Ozdil; Hikmet Akkiz; Can Kece; Macit Sandikci (Canadian Journal of Gastroenterology)
Leiomyomas are the most common benign mesenchymal tumours of the upper gastrointestinal tract. They rarely cause symptoms when they are smaller than 5 cm in diameter. Observation with repeated endoscopies is recommended in asymptomatic patients with small lesions. Surgical resection remains the main therapy option for symptomatic and complicated patients. The treatment of esophageal leiomyoma has been enhanced by improvements in diagnostic and therapeutic endoscopic techniques; however, the same cannot be said for gastric leiomyoma management. The present article describes the management of two cases involving giant gastric leiomyomas that were successfully treated using endoscopic injection of alcohol. To the authors’ knowledge, the present study is the first report of the treatment of such hemorrhagic gastric tumours using this alternative and low-cost technique. Endoscopic local ethanol injection may be the treatment of choice in carefully selected patients with hemorrhagic leiomyomas of the upper gastrointestinal tract.